ANALISIS STUDI PENELUSURAN (TRACER STUDY) ALUMNI PROGRAM STUDI MAGISTER PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TANJUNGPURA - Mandala, Yoga; Asriati, Nuraini; Syamsuri, Syamsuri (Universitas Tanjungpura, 2023)
This study aims to examine and analyze Educational History, Employment history, competence and competitiveness, relevance of education and work, learning experiences of alumni of the master of economic education study program FKIP Untan. This form of research is quantitative descriptive research with a type of Survey research. The samples in this study were graduates of TS-2 to TS master's study program in Economic Education FKIP Untan with a total of 13 alumni. The sampling method is Total Sampling. Data were collected with questionnaires that had been tested for validity by experts. The results of this study show that the Educational History based on the GPA of alumni is entirely 3.00, the waiting period for alumni work is on average 2-2.5 years, in filling the waiting period for the work of trade alumni, entrepreneurs, honoraries and others. Alumni work history is Most alumni work as teachers / educators in private and public schools with a salary of Rp1,000,000 to Rp5,000,000, this job is obtained through the internet or connection (friends and family) actively searching for themselves. The competence and competitiveness of alumni measured by various competencies have been considered good, the relevance of education and work is considered to be relevant between education and work, the contribution of learning experience in the master's study program economic education is largely very important in the world of work.